Ethical Consequentialism in Values and Principles of UNESCO’s Recommendation on the Ethics of Artificial Intelligence - Pasopati, Rommel Utungga; Bethari, Chili Podang; Nurdin, Dewi Syifanaya Firdausy; Camila, Myrilla Shafa; Hidayat, Sanjaya Ahmad (Proceeding International Conference on Religion, Science and Education, 2024)
This article exposes the matter of ethical consequentialism in values and principles of UNESCO’s Recommendation on the Ethics of Artificial Intelligence in 2021. By asserting qualitative approach through explorative method, this paper accentuates the matter of utilitarian perspective in dealing with the various developments of Artificial Intelligence. It is also done to answer the question of ‘how may consequentialism be reflected on the values and principles of UNESCO’s Recommendation on the Ethics of Artificial Intelligence?’. In analysis, the recommendations are indeed such reactions to the recent development of AI. The utilitarian aspect in that recommendation brings advantages to the existing spread of the usage of AI by not objectifying, undermining, and violating human rights. Consequentialism also widens matters of deontological points by being more flexible to see the process and the desired results. In conclusion, consequentialism may be necessary since it is done to prevent any worse condition regarding to ethical spread of AI. It must also be supplemented with intention to widen any coverage of AI worldwide so that enhanced moral considerations could always be attained.